The Impact of Social Media Marketing on Brand Awareness, Brand Engagement and Purchase Intention in Emerging Economies - Hassan Daghwi Obaid (Green Economics: International Journal of Islamic and Economic Education, 2025)
Abstract: This study investigates the impact of social media marketing (SMM) on brand awareness,brand engagement, and purchase intention across five emerging European economies: Albania,Kosovo, Romania, Ukraine, and North Macedonia. Anchored in the Uses and Gratifications Theory(UGT) and the Consumer Brand Engagement (CBE) model, the research employs Partial LeastSquares Structural Equation Modeling (PLS-SEM) to examine the complex interrelationships amongthese constructs. Findings reveal that SMM positively influences brand awareness and engagement,both of which significantly mediate the relationship between SMM and purchase intention.Importantly, the strength and nature of these effects vary by country, underscoring the role ofcultural and contextual factors in shaping consumer responses to digital marketing stimuli. Thiscross-national analysis fills a critical gap in the literature by focusing on underrepresented, highgrowth markets and offers valuable implications for both theory and practice. Specifically, itadvocates for localized, culturally sensitive SMM strategies that emphasize both visibility andinteractive engagement. The study contributes to the broader marketing discourse by demonstratinghow consumer behavior in digitally connected, developing economies diverges from that in maturemarkets, thereby reinforcing the necessity of context-aware digital marketing frameworks in globalstrategy formulation.